The Youth Leaving in the Amawiyan poetry (A model of AlA'arji and Al_ Ahwass) -A crytical Analysis- (Damascus University Journal of arts and humanities sciences, 2021)
This research deals with (the scene of youth leaving in the poems of Al_A'arji and Al_Ahwass). It starts with an introduction to present the main beginnings of such an essential issues during the history of the Arabic poet from Al_Jahilli till the Amawiyan Eras. The soul and mentality of the Arabian poet were being affected by the increasing of age, its misery feeling and the youth leaving; for that, this research represents the poetry of Al_A'arji and Al_AhwassAl_Ansari as a main model because of the great resemblance in accordance with their poetic styles. Also the introduction clarifies Dr. TahaHussain in his book (the Wednesday speech) because there also exist many points of differences, so there could make a specific study between them. This study aims to stand on the scene of youth leaving by analysing many poetic samples and studying some of their phenomenal artistic ideas such as (the conversation) and (the image resources of both of them ). Also the research would discover the reaction of Al_A'arji and Al_Ahwass towards the feeling of age increasing as shown within.
Keywords: The Youth Leaving in the Amawiyan poetry (A model of AlA'arji and Al_ Ahwass) -A crytical Analysis-